2017
DOI: 10.3389/fped.2017.00021
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Palsy—Trends in Epidemiology and Recent Development in Prenatal Mechanisms of Disease, Treatment, and Prevention

Abstract: Cerebral palsy (CP) is the most common motor disability in childhood. This syndrome is the manifestation of intrauterine pathologies, intrapartum complications, and the postnatal sequel, especially among preterm neonates. A double hit model theory is proposed suggesting that an intrauterine condition along with intrapartum or postnatal insult lead to the development of CP. Recent reports demonstrated that treatment during the process of preterm birth such as magnesium sulfate and postnatal modalities such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
211
0
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(237 citation statements)
references
References 106 publications
2
211
0
24
Order By: Relevance
“…RESULTS Thirty-three non-ambulatory patients ( The prevalence of cerebral palsy (CP) is estimated from 1.5 to more than 4 in every 1000 live births worldwide, and is thereby the most common physically disabling condition in childhood. 1 Dyskinetic CP accounts for 6% to 15% of all children with CP and is the most disabling form of CP. 2 Children with dyskinetic CP experience limitations in mobility, manual ability, and communication due to involuntary movements.…”
Section: Methodsmentioning
confidence: 99%
“…RESULTS Thirty-three non-ambulatory patients ( The prevalence of cerebral palsy (CP) is estimated from 1.5 to more than 4 in every 1000 live births worldwide, and is thereby the most common physically disabling condition in childhood. 1 Dyskinetic CP accounts for 6% to 15% of all children with CP and is the most disabling form of CP. 2 Children with dyskinetic CP experience limitations in mobility, manual ability, and communication due to involuntary movements.…”
Section: Methodsmentioning
confidence: 99%
“…Research has revealed some contentiousness on the role of birth asphyxia being either a relatively rare cause [24] or being a principal risk factor for CP [25]. Common risk factors in the post-neonatal period involve: infection (such as meningitis/encephalitis or severe infection and subsequent severe dehydration), head injury (such as those induced from traffic accidents, other traumatic injury, or non-accidental injury), vascular episodes (such as post cardiac or brain surgery), as well as other events (such as near drowning or near sudden infant death) [4]. Nonetheless, according to a recent systematic review by McIntyre and colleagues, 10 out of 38 risk factors were consistently associated with a statistically significant (p<0.05) risk of CP in infants.…”
Section: Common Risk Factors For Cp Development For High and Low-incomentioning
confidence: 99%
“…The average age for diagnosis is about 18 months; latest evidence suggests that cerebral palsy can be detected as early as three to four months using tests such as Prechtl's Qualitative Assessment of General Movements and magnetic resonance imaging [2]. As of today, CP remains a clinical description, but registries and surveillance programs, such as those in Australia, United Kingdom, and Europe, highlight five main elements reflecting the essential features of cerebral palsy, provided in definitions, and proposed by the SCPE: (i) it is an 'umbrella term'; (ii) it is permanent but not invariable; (iii) it involves restriction disorder of movement, posture, motor function, or a combination; (iv) it is attributed to a non-progressive interference, lesion, or abnormality; and (v) the interference, lesion, or abnormality arising in the developing or immature brain [3,4]. The exact etiology of this pathology remains unknown, although some research suggests that the mother's health, environmental, genetic and different ante, peri and post-natal factors could underlie the development of CP.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth is a major determinant of neonatal mortality and morbidity (Beck et al ., ). Remarkably, due to advances in neonatal intensive medicine and care, the survival rates of infants born very preterm (≤33 weeks gestation) and/or with very low birthweight (≤1,500 g) (VPT) have increased over the last decade (Aarnoudse‐Moens et al ., ; Arpi & Ferrari, ), but the prevalence of severe impairments, such as cerebral palsy, has stayed constant in recent years (Oskoui, Coutinho, Dykeman, Jetté, & Pringsheim, ; Stavsky et al ., ).…”
Section: Introductionmentioning
confidence: 97%